2018
DOI: 10.1002/jper.18-0468
|View full text |Cite
|
Sign up to set email alerts
|

Hypermobile upper lip is highly prevalent among patients seeking treatment for gummy smile

Abstract: Background Excessive gingival display (EGD), or a gummy smile (GS), is a mucogingival deformity that can be of concern to patients. The prevalence of GS etiologies, such as altered passive eruption (APE) and hypermobile upper lip (HUL), has not been reported. The aim of this study was to assess the prevalence of APE and HUL in patients seeking to correct their GS, and to determine possible prevalence differences among patients with different gingival display (GD) levels. Methods During clinical screening of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 32 publications
(94 reference statements)
2
39
0
7
Order By: Relevance
“…And it is often present in combination with other etiological factors. 26 In the present case HUL along with a moderate amount of vertical maxillary excess resulted in excessive display of the gingiva during smiling.…”
Section: Discussionmentioning
confidence: 44%
“…And it is often present in combination with other etiological factors. 26 In the present case HUL along with a moderate amount of vertical maxillary excess resulted in excessive display of the gingiva during smiling.…”
Section: Discussionmentioning
confidence: 44%
“…(9) Orthognathic surgery (10), botulinum toxin application on the muscles that regulate smiling (11), myotomy (12,13), gingivectomy (14) and lip repositioning (15)(16)(17) are methods that are used in GS treatment. A study on patients with complaints of GS reported that hypermobile upper lip syndrome was the most dominant etiological factor that led to GS by itself in approximately 45.3% of the patients and alongside passive eruption in approximately 34% of patients (18). Lip repositioning (LR) operation, which aims to reduce the amount of gingival visibility by restricting the movements of the muscles that lift the lip in treatment of GS caused by hypermobile upper lip, was performed for the first time in 1973 by Rubinstein (19).…”
Section: Introductionmentioning
confidence: 99%
“…Uma das principais queixas estéticas dos pacientes é o chamado sorriso gengival, que se caracteriza especialmente por exposição excessiva de gengiva no sorriso. Diferentes fatores estão envolvidos na etiologia do SG, sendo os principais: excesso vertical de maxila, erupção passiva e/ou ativa alterada, comprimento curto do lábio superior, hipermobilidade do lábio superior e, em alguns casos, hiperplasia gengival inflamatória e/ou hereditária (WU et al 2010;HUMAYUN 2010;CHU et al 2012;MIRON et al 2012;BHOLA et al 2015, BYNUM 2016ANDIJANI et al 2018). Embora os estudos reconheçam que a etiologia do sorriso gengival é multifatorial e apresentem propostas para a realização do diagnóstico e plano de tratamento associado à causa (TJAN et al 1984;GARBER, SALAMA 1996;DONG et al 1999;CHU et al 2004;MONACO et al 2004;AHMAD 2005;SABRI 2005;ZACHRISSON 2008;MIRON et al 2012;BHOLA et al 2015;BYNUM 2016;PAVONE et al 2016), nenhum deles apresenta um protocolo clínico e/ou de diagnóstico por imagens que seja capaz de identificar o principal fator etiológico do sorriso gengival, sendo este o objetivo primário deste estudo visto que, para se atingir resultados de tratamento satisfatórios para o paciente e para o profissional, é necessário primeiramente determinar a causa (BHOLA et al 2015;BYNUM 2016;PAVONE et al 2016).…”
Section: Discussionunclassified
“…A exposição de mais de 3mm de gengiva é apontada como pouco atrativa pela maioria dos profissionais e pacientes (KERNS et al 1997;KOKICH et al 1999;FLORES-MIR et al 2004;GERON, ATALIA 2005;IOI et al 2010). A exposição gengival excessiva durante o sorriso ("gummy smile" ou "sorriso gengival") é um problema estético que afeta mais mulheres do que homens, com prevalência de aproximadamente 10,5% da população na faixa etária de 20 a 30 anos, sendo 2 vezes mais frequente em mulheres do que em homens (TJAN et al 1984;RISGBEE et al 1988;PECK et al 1992;DONG et al 1999;ANDIJANI et al 2018 ).…”
Section: Introductionunclassified
See 1 more Smart Citation